2004
DOI: 10.1016/j.physb.2003.11.078
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle relaxation rate and shear viscosity of superfluid -A1 at low temperatures

Abstract: Quasiparticle relaxation rate,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Independent theoretical studies of the shear viscosity in the A 1 phase are in agreement with the experiments. 56,57) An independent shear viscosity measurement was made by Akimoto et al 58) with a torsional oscillator in magnetic fields below 12 T at various pressures below the melting pressure in a well controlledl l texture geometry. The temperature dependence at a given magnetic field was qualitatively similar to the Leiden results at melting pressure.…”
Section: Shear Viscositymentioning
confidence: 99%
“…Independent theoretical studies of the shear viscosity in the A 1 phase are in agreement with the experiments. 56,57) An independent shear viscosity measurement was made by Akimoto et al 58) with a torsional oscillator in magnetic fields below 12 T at various pressures below the melting pressure in a well controlledl l texture geometry. The temperature dependence at a given magnetic field was qualitatively similar to the Leiden results at melting pressure.…”
Section: Shear Viscositymentioning
confidence: 99%
“…Experimental evidence can be presented showing Pfitzner procedure is preferable to s-p approximation. Actually, in viscosity calculations of the A 1 -phase of superfluid 3 He (both at low temperatures [23,24,26] and near T c↑ [25]), applying Pfitzner procedure gave rise to a result compatible with the experiment. This strengthens the idea that Pfitzner procedure serves the purpose of the present case of study better than s-p approximation does.…”
Section: Application Of Boltzmann Equationmentioning
confidence: 72%
“…The transport properties such as the spin diffusion coefficients in the anisotropic A 1 -phase are highly desirable [6,22]. Some of transport coefficients of A 1 -phase have been derived both theoretically and experimentally; for example, viscosity at low temperatures and near critical temperature has been theoretically obtained [23][24][25][26] and a number of viscosity measurements have been carried out in a variety of high magnetic fields [27]. Also, thermal conductivity of A 1 -phase at low temperatures has been calculated theoretically, and as far as I am informed, there has been no data available about thermal conductivity of A 1 -phase [26,28,29] thus far.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also consider normal-superfluid interactions which come from the scattering between superfluid quasiparticles in the spin-up population, the so-called Bogoliubov quasiparticles and the normal fluid quasiparticles in the spin -down population. It is mentioned that, at low temperatures, we have shown that only normal-Bogoliubov quasiparticles interaction is important [3,4]. Also, however the number of the quasiparticles in superfluid is not fixed (and then some other processes such as decay and coalescence can occur), at low temperatures it has been shown that just the binary process are dominant [3][4][5].…”
mentioning
confidence: 82%